"Hooliganism" from Students' Point of View of Imam Abdulrahman bin Faisal University (Journal of Namibian Studies : History Politics Culture, 2023)
The research aims to identify the hooliganism of sports intolerance and the most important factors of a social and economic nature affecting the events of acts of intolerance in Saudi sports stadiums from the point of view of the students at Imam Abdulrahman bin Faisal University in Dammam by answering the following two questions: What is the hooliganism of sports intolerance? And what are the most important factors of a social and economic nature affecting the events of acts of intolerance in Saudi sports stadiums from the point of view of the students at Imam Abdulrahman bin Faisal University in Dammam. The researcher used the descriptive approach (survey studies) for its relevance to the study. The descriptive approach (survey studies) was used for its suitability and the nature of the study procedures. The study sample consists of (500) students from Imam Abdulrahman bin Faisal University in Dammam, who were randomly selected from among the various collages of the university for the scientific and humanitarian major for the academic year 2021/2022. A questionnaire was designed to identify the actual reality of hooliganism of sports intolerance from the point of view of the students at Imam Abdulrahman bin Faisal University in Dammam. Researcher presented the questionnaire in its initial form to (10) experts in the field of sports psychology and sports management in order to identify the validity of the content of the questionnaire through the arbitrators, as well as to identify the appropriateness of the questionnaire phrases. The results shows that the difference in the technical level of referees from one to another, and that the sports media, visual or audio, have a major and vital role in the hooliganism of sport, and the culture of the individual and his social upbringing and the lack of public awareness of good sports and sportsmanship affect sports hooliganism.